Risk Reduction Study of Hong Kong Index Futures - Lao, Yufei (2010)
The author uses the method of OLS to exam the hedging effectiveness of Hang Seng Index futures and Hang Seng H-share index futures. We find out that to a specify stock TraHK, during the period 1st March 2006 to 1st March 2008, the Hang Seng Index futures can perform better. One import finding through the OLS tests is that the hedge ratios are close to 1. According to that, it is interest to discover that the rate of return on the unhedged portfolio is equal to the return on futures. And generally speaking, the R2 of these regressions are satisfied, they are above 80% except the hedging strategy using H-share index futures. Then, the author uses two adjusted hedging strategy to test the hedging effectiveness of Hang Seng H-share index futures. The report point out it is useful to enhance the hedging performances by using a lagged model. It is because of the lagged respond of HHI to the changing economic environment. The report of a stop-lossing strategy also shows a better output. With this strategy, the author find out the near-month HHI futures’ hedging effect is improved a lot. The author argues that the dynamic hedging ,which has turn the relationship of HHI and TraHK to be more accurately, may contribute to this development of risk minimum.